The collective consciousness of an RE department during curriculum change: scripture, representation, science, fear and anger - Bowie, Robert A. (Journal of Religious Education, 2020)
This article reports a seed corn pilot study that presents a moment of the collective consciousness of an RE department in the midst of curriculum change. It records their concerns about the impact of increased content on depth in a new exam course, and the particular consequence this has for the kind of learning happening around texts. It reveals concerns about the representation of religion in the curriculum, the distance between that representation and teachers’ perceptions of pupils’ spiritual and religious lives. It also identifies teachers’ sense of fear and guilt about the challenge of fulfilling their duties to pupils, the secular authorities and the Catholic authorities, and reveals insights around the question of science and religion. In this single focus group, the collective consciousness of an RE department captures and illuminates many key issues of significance in RE today.